Analysis of the influence of hot rolled plate steel treatment using temper and quench-temper method on vickers hardness number enhancement - Taufik, Achmad; Pratikto, Pratikto; Suprapto, Agus; Sonief, Achmad As’ad (Eastern-European Journal of Enterprise Technologies, 2021)
This paper wants to know the effect of bending radius on the distribution of hardness, grain distribution and microstructure on the surface area of tensile stress and compressive stress after bending, quenching and tempering. Material testing helps determine and analyze material quality. The research was conducted on the bending of Hot Rolled Plate Steel material with a radius of 50 mm, 55 mm, 60 mm, 65 mm and 70 mm with a measurement distance of 1 mm, 2 mm and 3 mm, the highest value was obtained at a radius of 55 mm with a measurement distance of 1 mm. After getting the quench-temper treatment with a holding time of 30 minutes, the value of 498 HV was obtained at a radius of 70 mm with a measurement distance of 2 mm. Hardness test was performed using the austenite temperature of 900 °С, microstructure test results obtained finer grains in the compression area r=2.173 µm and in the tensile area r=2.34 µm. This observation aims to determine the microstructure of the material undergoing a heat treatment process at a temperature of 900 °С with a holding time of 30 minutes using water cooling media. The results of the observation of the microstructure of the test specimens before the quench-temper process showed that the structure of ferrite was more abundant than perlite, but after the quench-tempering process the results showed that there was more perlite than ferrite due to the presence of austenite. The treatment on the transformation of the Ar3 line causes the hardness to change the shape of the martensite microstructure into steel while the thickness of the carburizing layer increases with the increase in the carbonization temperature on the surface of the quenched specimen, resulting in the formation of martensite and residual austenite causing the coating to become hard.